Dysbiosis in a canine model of human fistulizing Crohn's disease. Issue 1 (9th November 2020) - Maldonado-Contreras, Ana; Ferrer, Lluís; Cawley, Caitlin; Crain, Sarah; Bhattarai, Shakti; Toscano, Juan; Ward, Doyle V.; Hoffman, Andrew
ABSTRACT: Crohn's disease (CD) is a chronic immune-mediated inflammatory condition caused by the loss of mucosal tolerance toward the commensal microbiota. On average, 29.5% and 42.7% CD patients experience perianal complications at 10 and 20 y after diagnosis, respectively. Perianal CD (pCD) result in high disease burden, diminished quality of life, and elevated health-care costs. Overall pCD are predictors of poor long-term outcomes. Animal models of gut inflammation have failed to fully recapitulate the human manifestations of fistulizing CD. Here, we evaluated dogs with spontaneous canine anal furunculosis (CAF), a disease with clinical similarities to pCD, as a surrogate model for understanding the microbial contribution of human pCD pathophysiology. By comparing the gut microbiomes between dogs suffering from CAF (CAF dogs) and healthy dogs, we show CAF-dog microbiomes are either very dissimilar (dysbiotic) or similar (healthy-like), yet unique, to healthy dog's microbiomes. Compared to healthy or healthy-like CAF microbiomes, dysbiotic CAF microbiomes showed an increased abundance of Bacteroides vulgatus and Escherichia coli and a decreased abundance of Megamonas species and Prevotella copri . Our results mirror what have been reported in previous microbiome studies of patients with CD; particularly, CAF dogs exhibited two distinct microbiome composition: dysbiotic and healthy-like, with determinant bacterial taxa such as E. coli and P. copri that overlap what it has been found on their human counterpart. Thus, our results support the use of CAF dogs as a surrogate model to advance our understanding of microbial dynamics in pCD.